2021
DOI: 10.15252/embr.202051009
|View full text |Cite
|
Sign up to set email alerts
|

Succinylation of H3K122 destabilizes nucleosomes and enhances transcription

Abstract: Histone post‐translational modifications (PTMs) are key players in chromatin regulation. The identification of novel histone acylations raises important questions regarding their role in transcription. In this study, we characterize the role of an acylation on the lateral surface of the histone octamer, H3K122 succinylation (H3K122succ), in chromatin function and transcription. Using chromatin succinylated at H3K122 in in vitro transcription assays, we show that the presence of H3K122succ is sufficient to stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 64 publications
1
51
0
Order By: Relevance
“…Enzymes utilize other cofactors, mainly depending on the size of acyl groups confirming the recent studies that the active sites in p300 and KAT2A are structurally incompatible with long‐chain acyl donors 50,51 . Lara Zorro Shahidian et al also suggested that p300/ CBP can succinylate H3K122 preferentially with acetyl‐CoA 28 …”
Section: The Structure and Function Of Histone Ksuc In The Nucleosomementioning
confidence: 59%
See 4 more Smart Citations
“…Enzymes utilize other cofactors, mainly depending on the size of acyl groups confirming the recent studies that the active sites in p300 and KAT2A are structurally incompatible with long‐chain acyl donors 50,51 . Lara Zorro Shahidian et al also suggested that p300/ CBP can succinylate H3K122 preferentially with acetyl‐CoA 28 …”
Section: The Structure and Function Of Histone Ksuc In The Nucleosomementioning
confidence: 59%
“…It also verified a strong correlation between gene expression and protein succinylation near the transcriptional start site by showing a correlation between the succinyl‐lysine ChIP signal and gene expression, which further indicates that promoter succinylation is a mark of gene transcriptional activity 27 . Recently, it was also found that H3K122succ is enriched at transcription start sites and can be a mark of active genes, stimulating transcription in vitro and changing the structure of the stable nucleosome 28 …”
Section: The Structure and Function Of Histone Ksuc In The Nucleosomementioning
confidence: 64%
See 3 more Smart Citations